사이코드라마가 가정폭력 피해여성의 자존감, 안녕감, 불안, 우울에 미치는 효과 - 박진아; Park Jin Ah; 성은옥; Sung Eun Ok (한국사이코드라마학회지, 2018)
본 연구는 쉼터에 입소한 가정폭력 피해여성을 대상으로 사이코드라마를 시행하고 자존감, 안녕감, 불안, 우울에 미치는 효과를 확인하고자 하는 목적으로 시도되었다. 자료는 2015년 1월 4일부터 2월 26일까지 가정폭력 피해자 보호시설 입소자 7명을 대상으로 10회의 사이코드라마를 시행하였고, 사전-사후 설문을 통하여 수집하였다. 자료분석은 SPSS 22.0 프로그램을 사용하여 빈도, 백분율, 피어슨 상관계수, Wilcoxon의 부호 순위검정을 하였다. 그 결과 대상자의 자존감은 불안(r=-.866, p =.012), 우울(r=-.824, p =.023)과 음의 상관관계를, 불안은 우울(r=.778, p =.040)과 양의 상관관계를 나타냈으며, 사이코드라마 시행 전·후 자존감, 안녕감, 불안 우울은 통계적으로 유의한 차이를 나타내지 못했지만 자존감과 안녕감의 사후점수가 상승하였고, 불안과 우울의 사후점수는 감소했음을 확인할 수 있었다. 가정폭력피해여성의 자존감과 안녕감을 증진시키고 불안과 우울을 감소시키기 위해서는 여가 및 심리지원 프로그램의 적용 및 사이코드라마에 계속적인 참여를 위한 장기 지원프로그램이 필요하다. The purpose of this study was to investigate the effects of psychodrama on self - esteem, well - being, anxiety and depression among domestic violence victims who entered the shelter. This study is a similar experimental study of a single group preand post-design. Data were collected from 7 participants, pre - post - questionnaire surveys conducted ten times psychodrama, during the period from January 4 to February 26, 2015. Data were analyzed using frequency, percentage, Pearson correlation coefficient and Wilcoxon 's sign rank test using SPSS 22.0 program. As a result, the participants' self-esteem was negatively correlated with anxiety(r=-.866, p =.012), depression(r=-.824, p =.023). There was no statistically significant difference in self-esteem, well-being, and anxiety, depression between before and after the psychodrama, but there was an increase in post-score of self-esteem and well-being, and the post-score of anxiety and depression decreased. In order to improve the self-esteem and well-being and to reduce anxiety and depression in women victimized by domestic violence, long-term support programs are needed for the application of leisure and psychological support programs and continuous participation in psychodrama.